Mekong Scales: Domains, Test Sites, and the Uncommons - Jensen, Casper Bruun (Anthropologica, 2017)
Inspired by Marilyn Strathern's fractal analyses, this article develops the notions of domain and scale making as a way of conceiving the Mekong uncommons. Juxtaposing the perspectives and activities of community forestry and ecotourism in Kratie Province with policy controversies concerning dam development on the Laos-Cambodia border, I depict each domain as an ontological test site that scales reality in its own distinctive way. Despite their incongruence, these scales gradually become interwoven due to the interactions of domains. These interactions make up the continuous actual becoming of Mekong realities. Rather than conforming to any general ontological schema, however, the outcome is the emergence of divergent, only partly commensurable, practical ontologies. Instead of adding up to a “whole” Mekong, what comes into view is the proliferation of the Mekong uncommons.